2016
DOI: 10.4103/0976-237x.183047
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness of bleached enamel: Effect of applying three different nanobiomaterials by nanoindentation test

Abstract: Background:Despite the absence of dispute about the efficacy of bleaching agents, a prime concern is about their compromising effect on the enamel structure. This in vitro study investigated whether the addition of three different biomaterials, including nano-bioactive glass (n-BG)/nano-hydroxy apetite (n-HA)/nano-amorphous calcium phosphate (n-ACP), to bleaching agents can affect the fracture toughness (FT) and vickers hardness number (VHN) of bovine enamel.Materials and Methods:The crowns of the newly extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…showed in an in vitro study that a gentle, noninvasive bleaching procedure by incorporating three different biomaterials, including nano-BAG, nano-hydroxyapatite, and nano-amorphous calcium phosphate, into bleaching agents might mitigate the negative effects of tooth bleaching and prevent the irreversible changes in the enamel surface. [ 99 100 ] This treatment modality should be reserved for patients with good oral hygiene to mask inactive lesions when natural remineralization is not complete. [ 92 ]…”
Section: After the Orthodontic Treatmentmentioning
confidence: 99%
“…showed in an in vitro study that a gentle, noninvasive bleaching procedure by incorporating three different biomaterials, including nano-BAG, nano-hydroxyapatite, and nano-amorphous calcium phosphate, into bleaching agents might mitigate the negative effects of tooth bleaching and prevent the irreversible changes in the enamel surface. [ 99 100 ] This treatment modality should be reserved for patients with good oral hygiene to mask inactive lesions when natural remineralization is not complete. [ 92 ]…”
Section: After the Orthodontic Treatmentmentioning
confidence: 99%
“…It was already demonstrated that adding remineralizing agents such as CPP-ACP paste, fluoride, and nano-biomaterials to bleaching gels enhances the mineral deposition, induces fluoride acquisition and prevents irreversible changes on enamel without altering the whitening efficacy. 16 24 26 27 28 29 30 While, in GI (35% HP Whiteness HP Maxx) the microhardness increase is thought to be related to the short application time of the bleaching gel and the early contact with saliva. Artificial saliva, following the literature, can boost the remineralization and increase enamel microhardness subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be stressed that such materials are generally employed with no follow-up or technical supervision, raising concerns in the scientific community. This is especially true when considering the abrasiveness of these products and their possible morphological changes and negative effects, such as increased toothsensitivity and compromised enamel structure 4 , 7 - 10 . Furthermore, patients with severe discoloration, such as tetracycline staining and fluorosis, may believe that the products will solve their problem instead of seeking professional help.…”
Section: Introductionmentioning
confidence: 99%